Modification of multimetallic naphtha-reforming catalysts by indium addition - Benitez, Viviana Monica (2009)
Pt-Re-Ge/Al2O3 and Pt-Re-Sn/Al2O 3 trimetallic naphtha-reforming catalysts were modified by the addition of indium. This additive negatively modified both the acid and metal functions of the catalysts. It produced a decrease in the activity in acid-catalyzed reactions such as the isomerization of n-pentane. Metal catalytic properties were inhibited, and the capacity for CO chemisorption also decreased. © 2009 American Chemical Society.